Costs of bleeding on long-term antiplatelet treatment without routine co-prescription of proton-pump inhibitors - Luengo-Fernandez, R; Li, L; Rothwell, PM (SAGE Publications, 2019)
Background: Long-term antiplatelet treatment is associated with major bleeding.